Developing microtakaful flood model in Malaysia - Its relevance and policy impacts - Wan Norhayate, Wan Daud; Ahmad Shukri, Yazid; Fauzilah, Salleh; Fakhrul Anwar, Zainol (2016)
Flood is the largest natural disaster occurrence in Malaysia and is expected to exacerbate due to the various extreme weathers in the country. Despite the high risk of flood, flood coverage insurance policy is not always available. To overcome this challenge, this study attempts to achieve two objectives: first, to examine the impact of flood risk to the affected community, and second to develop a model called the microtakaful flood model to help the flood victims among the poor community. This qualitative research focuses on multiple case studies. The study found that there is a need for the poor to be insured with the flood coverage in order that they can resume a normal life with less difficulty post-flood catastrophe. The results of this study provide a significant contribution by introducing the microtakaful flood scheme to the industry that could reduce the government’s burden as a result of the flood loss.